A rat model of a focal mosaic expression of PCDH19 replicates human brain developmental abnormalities and behaviours. Issue 3 (5th April 2022) - Cwetsch, Andrzej W.; Ziogas, Ilias; Narducci, Roberto; Savardi, Annalisa; Bolla, Maria; Pinto, Bruno; Perlini, Laura E.; Bassani, Silvia; Passafaro, Maria; Cancedda, Laura
Abstract: Protocadherin 19 gene-related epilepsy or protocadherin 19 clustering epilepsy is an infantile-onset epilepsy syndrome characterized by psychiatric (including autism-related), sensory, and cognitive impairment of varying degrees. Protocadherin 19 clustering epilepsy is caused by X-linked protocadherin 19 protein loss of function. Due to random X-chromosome inactivation, protocadherin 19 clustering epilepsy-affected females present a mosaic population of healthy and protocadherin 19-mutant cells. Unfortunately, to date, no current mouse model can fully recapitulate both the brain histological and behavioural deficits present in people with protocadherin 19 clustering epilepsy. Thus, the search for a proper understanding of the disease and possible future treatment is hampered. By inducing a focal mosaicism of protocadherin 19 expression using in utero electroporation in rats, we found here that protocadherin 19 signalling in specific brain areas is implicated in neuronal migration, heat-induced epileptic seizures, core/comorbid behaviours related to autism and cognitive function. Abstract : Cwetsch et al . report a rat model of focal brain mosaicism of PCDH19 downregulation induced by in utero electroporation, aimed at mimicking the X-linked inheritance pattern of PCDH19-CE people. A local mosaic of Pcdh19 downregulation resulted in brain development deficits, heat-induced epileptic seizures, autism-related behaviors, and reduced cognitive performance. Graphical Abstract: Graphical Abstract